Reformulation of Restitution Arrangements for Children Who Become Victims of Sexual Violence Crimes to Realize the Best Interest of the Child - Muhammad Rendi; Rini Fathonah; Fristia Berdian Tamza (JURNAL MAHASISWA YUSTISI, 2026)
The principle of the best interest of the child requires that every legal policy place the best interests of the child as the primary consideration; however, the restitution arrangements for child victims of sexual violence crimes in Indonesia have not yet fully reflected this principle. This study aims to analyze restitution arrangements within Indonesian laws and regulations and to formulate a reformulation of legal policy that is more oriented toward victim recovery. The research method employed is normative juridical with statutory and case approaches, through an examination of the Child Protection Law, the Sexual Violence Crime Law, Government Regulation Number 43 of 2017, as well as relevant court decisions. The results of the study indicate that restitution has normatively been recognized as a victim’s right, yet its construction remains passive, procedural, and dependent upon applications submitted by victims or their companions. Such conditions have resulted in the minimal number of decisions containing restitution and demonstrate that the orientation of the judicial system still focuses more on punishing perpetrators rather than restoring victims. This study concludes that an urgent reformulation is necessary by transforming restitution into an active obligation of the state through mandatory claims by public prosecutors and the authority of judges to impose it ex officio in order to realize effective legal protection for child victims.